A Morphological Analysis of Verb Derivation from Adjectives in Bugis, English, And Javanese: An Interlingual Perspective with a Cultural Dimension - Hengki Hengki; Ratna Ratna; Nehru Pasoloran Pongsapan (CV. Rustam, 2026)
This study compares the morphological construction of verbs from adjectives in three typologically and genetically distinct languages: Bugis (Austronesian, spoken in South Sulawesi, Indonesia), Javanese (Austronesian, Central and East Java), and English. Using an interlingual and culturally informed approach, the study investigates 15 systematic adjective-verb pairings from different languages to find underlying derivational mechanisms, structural patterns, and the linguistic encoding of cultural values. The analysis shows unique morphological strategies: Bugis primarily uses verbalizing prefixes such as ma- and mam- often accompanied by phonological adjustments—demonstrating a tightly integrated system of affixation and reduplication; English relies heavily on zero derivation (conversion) and suffixation (e.g., -ize, -ify), reflecting its trend toward analyticity and syntactic flexibility; meanwhile, Javanese employs a complex system involving the prefix N- (with allomorphs like ng-, n-, m-) combined with the suf Crucially, the study shows that these morphological processes are not just grammatical, but also deeply embedded with cultural semantics—for example, the Bugis mappadeceng (